KEPASTIAN HUKUM PENERBITAN GANDA ATAS SERTIPIKAT HAK ATAS TANAH (Studi Kasus Putusan Nomor 307 K/Pdt/2008 Dan Putusan Nomor 976 K/ Pdt/2015) - Lymens Gho (Program Magister Ilmu Hukum Universitas Pancasila, 2022)
Indonesia has large tracts of land, the government provides opportunities for the public to manage these land parcels according to their needs, the community can register the land parcels they own with the National Land Agency, where the land parcels are located, to obtain one of the certificates. land rights, including: Certificate of Ownership Right, Certificate of Right to Build, Certificate of Use Right, Certificate of Cultivation Right or Land Certificate in the form of Girik. procedures for land registration are contained in Government Regulation Number 24 of 1997 concerning Land Registration. The National Land Agency or BPN is a non-departmental government agency whose duties include the land sector. To carry out the duties and functions of the National Land Agency or BPN in the regions, BPN Regional Offices are formed in provinces and Land Offices in districts or cities based on Presidential Regulation of the Republic of Indonesia Number 48 of 2020 concerning the National Land Agency. On one plot of land, only one type of certificate of land rights can apply, unless there is an agreement between the parties holding the certificate. These certificates issued by the National Land Agency have the force of law and are legal evidence of the rights owned by the party whose name is listed on the certificate. However, even though the registration has been carried out and the land title certificates have been issued, there is still a dispute over which party has the rights over the land parcels because there are two land title certificates issued by the National Land Agency for the same part of land